A biophysical perspective of food adulteration - Walaa Nasr Ali Ahmed Nasr; Ebtesam M. Abdelghany; Omar S. Desoukey; Wael M. Elshemey (Cairo : Walaa Nasr Ali Ahmed Nasr, 2019)
This work aims at examining the performance of suggested biophysical techniques for the detection of virgin olive oil (VOO) adulteration with corn oil (CO). In order to reach such purpose, the ability to characterize oils such as CO, Sunflower Oil (SFO) and VOO are studied using UV-visible spectroscopy, refractive index (RI) and Fourier Transform Infra-red (FTIR) spectroscopy techniques.Oils at room temperature show that VOO has characteristic peaks (at 450, 480 and 670 nm) that significantly characterize (p<0.05) VOO from the other two oils. Moreover, a shoulder at 340 nm for CO and SFO samples is almost absent in the case of VOO. Thus one can readily characterize VOO from CO and SFO, while the latter two oils have considerably similar spectra. After heating at frying temperature (190rC) for 2 hours, the characteristic peaks of VOO become completely absent and the spectra of the three oils become considerably similar. So, it is difficult to characterize the three oils from their UV-visible absorption spectra after being heated at 190rC.The RI measurements are efficient in the characterization of the three investigated vegetable oils (CO, SFO and VOO), where the RI of VOO appear to be significantly (p<0.05) lower than the RI for both CO and SFO
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Biophysics
Issued also as CD
Keywords: FTIR; RI; UV-visible Spectroscopy